Luteotropic roles of glucocorticoids in rat granulosa cells - Xin-Yan Huang; Yin-Yan Xu; Juan Xie; Li Wang (Reproductive and Developmental Medicine, 2020)
Objective: The study objective was to investigate whether endogenous glucocorticoids directly impact the functions and proliferation/apoptosis of ovarian granulosa cells. Methods: Primary rat ovarian granulosa cells were cultured and treated with graded concentrations of corticosterone either alone or in the presence of the indicated drugs. After 48 h of treatment, the cells and growth media were collected to measure intracellular and extracellular progesterone/estradiol concentrations, and steroid secretion ratios were obtained by parameter calculation. The number of granulosa cells was determined by Cell Counting Kit-8. To determine the impact on cell numbers, granulosa cell proliferation was detected using the BrdU incorporation method and cell apoptosis was detected by flow cytometry. Results: First, high corticosterone concentrations significantly stimulated progesterone synthesis/secretion and inhibited estradiol synthesis in cultured granulosa cells. Second, accompanied by follicle-stimulating hormone, high corticosterone concentrations promoted progesterone synthesis/release and estradiol release. Last, high corticosterone concentrations increased the cell number and suppressed apoptosis but did not induce cell proliferation. Conclusions: These indicate that high glucocorticoid concentrations may play luteotropic roles in the functions and number of corpora lutea.